HIGH-THROUGHPUT SIMULATIONS OF PROKARYOTIC COMMUNITY EVOLUTION WITH HAPLOID EVOLUTIONARY CONSTRUCTOR - Z. S. Mustafin; Yu. G. Matushkin; S. A. Lashin (Вавиловский журнал генетики и селекции)
The results of the development of a high-throughput version of the software package Haploid Evolutionary Constructor (HEC), available at http://evol-constructor.bionet.nsc.ru, are presented. The software is used to simulate the functioning and evolution of prokaryotic communities. A parallel version of the software package was created using the MPI technology. The test was performed on a cluster of the Bioinformatics shared access center. The acceleration obtained was almost linear. The simulation time of complex bacterial communities was reduced from dozens of hours to several minutes.